Profitability as a Moderating Variable of Systematic Risk in Mining Companies - Lasmana, Syaiful Andy; Wahyudin, Agus (Accounting Analysis Journal, 2021)
This study aims to examine the effect of liquidity, earning variability, and firm size on systematic risk with profitability as a moderating variable. Some 37 mining companies listed on the Indonesia Stock Exchange in 2014-2016 are selected as the population of this study. Total 26 companies with 78 units of analysis are obtained using the purposive sampling technique. The data analysis technique used is the method of testing the moderation regression model with the IBM SPSS 21 analysis tool. The results show that liquidity and firm size are not related to systematic risk while earning variability has a significant negative effect on systematic risk. The results of the moderation test prove that profitability does not significantly moderate the effect of liquidity on systematic risk, but moderates the effect of earning variability and firm size on systematic risk. This study concludes that systematic risk is affected by earning variability while profitability moderates the effect of earning variability and firm size on systematic risk. Keywords: Earning Variability; Liquidity; Profitability; Systematic Risk; Firm Size